Effect of short-term frozen storage of raw meat on aroma retention of chicken broth: A perspective on physicochemical properties of broth. (1st June 2022) - Qi, Jun; Yan, Hui-min; Xu, Ying; Peng, Ya-lin; Jia, Chuan-kang; Ye, Min; Fan, Zhi-hao; Xiong, Guo-yuan; Mei, Lin; Xu, Xing-lian
Abstract: The effect of short-term frozen storage (0, 2, 4, 6, and 8 wk) of raw meat on the aroma retention of chicken broth was discussed from a perspective on physicochemical properties of broth. With the increased storage time of frozen chicken, the protein concentration of the broth first increased and then decreased significantly due to changes in the small-molecule protein fractions (<10 kDa), as determined by SDS-PAGE. The volume fraction of oil droplets and the particle size increased significantly. Meanwhile, the absolute zeta potential decreased. The result from the circular dichroism spectrum showed that gelatin, the major structural protein in chicken broth, tended to depolymerize. In general, when the storage time of frozen chicken increased, the depolymerization of gelatin in the broth could enhance its emulsifying ability, resulting in the increases in the fat content and particle size of chicken broth, which enhanced the aroma retention of chicken broth. The information obtained could be used to explain the enhanced aroma strength of the broth prepared from chicken following short-term frozen storage. Highlights: Gelatin was the major structural protein of chicken broth. The depolymerization of gelatin molecules increased the fat content. Fat is the key factor affecting aroma retention of chicken broth.